Numerical studies on the dynamics of the Northwestern Black Sea shelf - KOURAFALOU, V.; TSIARAS, K.; STANEVA, J. (Mediterranean Marine Science, 2004)
The Northwestern Black Sea shelf dynamics are studied with numerical simulations based on the Princeton Ocean Model. The study focus is on buoyancy and wind driven flows and on the transport and fate of low salinity waters that are introduced through riverine sources (the Danube, Dnestr and Dnepr Rivers), under the seasonal changes in atmospheric forcing. The study is part of the DANUBS project (NUtrient management in the DAnube basin and its impact on the Black Sea). The numerical simulations show that the coastal circulation is greatly influenced by river runoff and especially that of the Danube, which is dominant with monthly averaged values ranging from 5,000 m3 to 10,000 m3. The transport of low-salinity waters associated with the Danube runoff is greatly influenced by wind stress, topographic effects and basin-scale circulation patterns, such as changes in the position of the Rim Current.